The Concept of Just and Civilized Humanity in the 2nd Principle as viewed from QS An Nisa Verse 58 According to Tafsir Quraish Shihab - Aldis, Bebi Arifah; Anwar, Husnel (Academy of Education Journal, 2024)
The large number of Indonesian people who do not practice the second principle, namely just and civilized humanity, makes this Pancasila useless. In fact, this second principle is also mentioned in surah an-nisa verse 58 and this verse has been confirmed by modern interpretations, one of which is the Al-Misbah interpretation. This research also compares Quraish Shihab's thoughts in his interpretation of Al-Misbah with Buya Hamka in his interpretation of Al-Azhar